The effect of rehabilitative exercises on the strength of the muscles of the partially dislocated shoulder of young basketball players (Journal of the College of Basic Education, 2023)
Summary of the research:The importance of the research enables the rehabilitative exercises to play a role in returning the players to the stadiums at the maximum speed while restoring their functional competencies in the shortest possible time to avoid complications as a result of this injury. The research problem is the large number of errors that result from the application of a training method for the game of basketball, lack of experience, practice and friction, and that This injury resulting from increased stress on the joints, muscles and tendons working on them, as well as not taking complete and sufficient rest for the state of recovery. Therefore, the researchers decided to study this problem in the preparation of rehabilitative exercises and the effect of these exercises in improving and restoring recovery for the dislocation injury in the shoulder joint of basketball players. The researchers used the experimental approach to design one group with two tests, pre and post, and the research sample consisted of (8) players from Baghdad clubs participating in the Iraqi Basketball League for the 2021-2022 season, and they were chosen by the intentional method. The researchers used the strength test of the shoulder joint on the research sample with two tests. The pre and post test for one group in favor of the post test and the results it reached using the statistical bag (Test), and the conclusions reached by the effect of the rehabilitative exercise program on developing the strength of the shoulder joint.Keywords: rehabilitative exercises - partial dislocation of the shoulder joint - strength.Youth basketball